Occupational Safety and Health in Floriculture: Analysis of Pesticide Effects - Villegas Narvaez , Lizbeth Mayte (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
The article reviewed the importance of occupational health and safety in the Ecuadorian flower sector, especially in relation to exposure to pesticides. These chemicals, essential for crop protection, have raised concerns due to their adverse effects on workers' health. Previous research that demonstrated significant risks and highlighted the need to improve labor practices and regulation of pesticide use was addressed.DevelopmentThe daily exposure of workers to phytosanitary products and its consequences on health was analyzed. The studies evaluated showed a high prevalence of neurological, respiratory, skin and, to a lesser extent, renal problems. Factors such as lack of personal protective equipment, poor working conditions and prolonged exposure to highly toxic chemicals were also identified. In addition, the acute and chronic effects of these substances were reviewed, as well as the preventive measures proposed in previous studies. Strategies included training, monitoring of working conditions and adoption of sustainable agricultural practices.ConclusionsThe article concluded that pesticide exposure represents a significant risk for flower workers in Ecuador. The implementation of safety measures and strict regulation of the use of these products are essential to protect their health. In addition, the need for further research on long-term effects and the promotion of a safer work culture was highlighted